Kesetaraan Hak Wanita Dalam Kemandirian Secara Finansial Menurut Hukum Ham Internasional Islam - Rury Octaviani; Shafiyah Rahmah (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The Organization of Islamic Cooperation made a declaration intended for member states and has been recognized by the United Nations as an instrument of international Islamic human rights called the Cairo Declaration. Article 6 of the Cairo Declaration enumerates the principle of equal rights of women in financial independence. In the current era of globalization, it encourages women to gain financial independence, but in reality women often get dishonorable treatment. Such as sexual harassment at work, on public transport and other public places. The purpose of this study is to find out why Islam emphasizes the need for financial independence in the perspective of international human rights and find the commitment of the Indonesian state as an OIC member state to take part in legal protection for women in order to fulfill women's financial independence. To achieve the objectives of this study, normative juridical research methods are used by conceptual approaching with the principle of gender equality. The expected recommendation is that the Islamic human rights perspective allows for financial independence with the permissible limitations in Islam. The Government of Indonesia fulfills international obligations not only as a member state of the OIC but also as a state party to international agreements governing the principle of women's equality.